Output Characteristics of Small Wind Power Generator with Three-layer Propeller Type Blade Structure - Yoo, Seak-Ju; Jeon, Jeong-Chay; Oh, Hun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Large wind power generate noise due to the high speed of their long wing tips, and are dogged by substantial investment cost due to cumbersome installation process that can be implemented only for large companies. It is necessary to develop low-cost, high-efficiency and small-sized wind power generator in order to address this problem, thereby enabling individual citizens to have their own wind power generator.Methods/Statistical analysis: This paper constructed an experimental system by using small wind power generator with three-layer propeller type blade made fromthree aluminum plates, which is 50cm length and 12cm wide, are made at an angle of 120 degrees. And output volatage, current, elecrtrical pwoer and RPM characteristics of small wind power generator according to Blade structure and wind speed.Findings: The experimental results show that output voltage, current and RPM of the wind generator with three-layered blade structure was increased by 36% and 17%, 42% and 18%, 34% and11% than the wind generator with one-layer blade and two-layer blade structure at maximum wind speed 10m/s, respectively. The proposed three-layered blade was generated at low wind speeds.Improvements/Applications: The proposed method is looking forward to playing an important role in solving the problems of the present wind power generation like as generation efficiency and expansion of distribution at inland areas having low wind speed.Â